Development of tools for the management of oyster nurseries: static and dynamic modelling - Soares, Filipe Miguel Ramos da Cruz (2017)
Ecological models have been applied for carrying capacity assessments of oyster aquaculture, and have shown to be very useful in guiding the planning and management towards production optimization. However, the existing models are mostly directed to the grow-out phase (production of adult oyster), lacking models to be applied in nurseries (production of juvenile oyster). This work presents two models to support the management of oyster nurseries that are targeted to farmers: - A static mass balance model for oyster nurseries, which estimates the maximum stock for typical external food concentrations of the nursery. Part of the work developed herein contributed to its development (available online at: http://seaplusplus4.com/oysterspatbud.html). - A dynamic model for oyster nurseries, which simulates the individual growth, food availability and stock evolution over time. The model was conceptualized and implemented as part of this work, and further validated with three data sets from the scientific literature. In this work, it is shown the application of both models to simulate a commercial nursery. The results show that both models can provide useful information, and thus guidance to farmers, even when there is a lack of data or knowledge about some features of the system, required to properly drive the models.